The regulation of administrative procedents in the peruvian legal system - Cairampoma Arroyo, Alberto (2014)
The importance of providing equal treatment to citizens, and of the predictability of public administration in resolving their disputes or requests is undeniable. In this context, the administrative precedent is an important tool to achieve the aforementioned objectives, allowing the performance of Public Administrations to provide legal certainty and avoid arbitrary situations.